Cardiovascular, anthropometric, metabolic and hormonal profiling of normotensive women with polycystic ovary syndrome with and without biochemical hyperandrogenism - Kałużna, Małgorzata (Endocrine, 2021)
PURPOSE: Women with polycystic ovary syndrome (PCOS) present with or without biochemical hyperandrogenism (HAPCOS or non-HAPCOS, respectively). Cardiometabolic and hormonal abnormalities have been reported in women with PCOS, particularly those with hypertension. However, no direct comparison between normotensive (blood pressure <140/90 mmHg) patients with HAPCOS and non-HAPCOS has been made. This study compared different cardiovascular (CV), anthropometric, metabolic and hormonal features between normotensive patients with HAPCOS and non-HAPCOS and healthy women. METHODS: We consecutively recruited 249 normotensive patients with PCOS and 85 healthy eumenorrheic women to a case-control observational study. Based on blood androgen concentration, patients with PCOS were divided into HAPCOS (n = 69) or non-HAPCOS (n = 180) groups. RESULTS: Although within normal ranges, patients with HAPCOS had significantly (p < 0.05) higher peripheral and central systolic blood pressure and pulse pressure, C-reactive protein, low-density lipoprotein cholesterol, triglycerides, glucose, and insulin than subjects with non-HAPCOS, and healthy women. They also had lower N-terminal prohormone of B-type natriuretic peptide (NT-proBNP) concentration. In contrast, their body mass index (BMI) was higher of over 4 kg/m(2) than patients with non-HAPCOS and nearly 6 kg/m(2) than in healthy participants. Except for BMI, statistical differences in the cardiometabolic profile were of little clinical relevance. CONCLUSIONS: Young normotensive women with HAPCOS have a worse cardiometabolic profile but lower NT-proBNP concentration than patients with non-HAPCOS. Features of this profile in both PCOS groups are within ranges typical for healthy women. Increased BMI is the only clinically relevant feature differentiating hyperandrogenic from non-hyperandrogenic patients with PCOS, and healthy women.